ON INTEGRAL OPERATORS OF BERGMAN TYPE ON THE UNIT BALL OF R^n - Tonoyan, Ye.G. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2015)
We prove the boundedness of Bergman type integral operators in mixed norm spaces over the unit ball of R^n. Bounded harmonic projections are found in the mixed norm and Lipschitz spaces. Corresponding Forelli–Rudin type theorems are proved.